Archetype Analysis Of The Main Character In Marc Forster’s Movie A Man Called Otto - Syamsul Bahri; Saralena Manik; Christy Aulia Dunov Simanjuntak; Yeni Adventry Tanjung; Jovan Morientes Nigel (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Literature and film often use universal character patterns, known as archetypes, to explore deep psychological and social themes that resonate across cultures. Recent studies have applied Jungian archetype theory to analyze characters in various films, but few have focused on how these patterns shape emotional journeys in contemporary drama. This study aims to examine the archetypal dimensions of the main character, Otto Anderson, in Marc Forster’s film A Man Called Otto by applying Carl Gustav Jung’s archetype theory. Using a descriptive qualitative method, the research analyzes selected scenes, dialogues, and monologues to identify and interpret five key archetypes: Self, Ego, Persona, Shadow, and Anima. The findings show that Otto’s character embodies all five archetypes, with the Ego (30,77%) and Shadow (23,08%) dominating his early isolation and emotional defenses, while the Self (11,54%), Anima (15,38%), Persona (19,23%) and emerge as he reconnects with others and moves toward healing. These percentages illustrate the varying influence of each archetype throughout Otto’s journey, highlighting how his psychological transformation is reflected in the shifting dominance of these archetypal patterns. Compared to previous studies that examined archetypes in films such as Enola Holmes, Mcfarland USA, Encanto, The Dark Tower, and The Three Stooges, this research offers a deeper psychological perspective by focusing on the interplay of grief, isolation, and transformation within a dramatic context. The analysis demonstrates the value of archetype theory in understanding character development and highlights how A Man Called Otto reflects universal experiences of loss and resilience in modern cinema.